Pembiayaan Murâbahah yang Bermasalah di Baitul Mâl Wa Tamwîl(BMT) XYZ Dalam Perspektif Manajemen Risiko - Rahma Yudi Astuti (University of Darussalam Gontor, 2015)
Baitul Mal wa Tamwil XYZ as microfinance institutions that run the operation works with Islamic principles, in which the principal activity in the form of funding and financing to the community, always filled with uncertainty. Murabaha is a financing product that is very popular in BMT XYZ. This is because these products are considered as a product that is easy to apply and has a relatively small risk. However murabaha product was not completely safe and risk-free. Recorded murabaha financing problems in BMT XYZ currently account for 15.8% of the total amount of financing is not fully influenced by the type of contract, but is also highly dependent on the nominal size of the financing, and long periods of financing as well as other variables listed in such financing and guarantee problems character client and intervention board on the performance of managers. Therefore we need a series of procedures and methodologies that can be used to measure, identify, monitor and control risks that arise. The research problems are why the Murabaha financing is problematic in BMT XYZ and how the steps are carried out by BMT XYZ against Murabaha financing is problematic.This research is a field (field research) that is descriptive qualitative. Data were collected through observation, documentation, and interviews, while the type of data used are primary data and secondary data. Based on the findings in the field can be seen that the factors causing the problem, namely murabaha financing from the customer and the factors BMT itself. Factors of customers due to the weak economic situation of customers, the business is not smooth, character weakness and turmoil. While the factor of BMT XYZ itself is weakness analysis and carelessness account officer in collecting and analyzing data in a prospective customer financing does not correspond to the actual state of the prospective customers. Violation of the LLL by the board and the change manager within a relatively short time. BMT effort XYZ against problematic Murabaha financing is a preventative measure, revitalizing and takeover of collateral. Meanwhile, to minimize the risk that the financing distribution strategy, a strategy of collection of receivables and collateral strategy and the implementation of the precautionary principle (prudential Banking).